Severe Microcytic Anaemia Due to Chohn’s Disease : An Uncommon Presentation - Islam, Mohammad Syedul; Irshadullah, Naseeb Mohammad; Md Jabed, Syed; Uddin, Rabiul Alam Md Erfan (Journal of Chittagong Medical College Teachers' Association, 2012)
Crohn’s disease is an uncommon disease. Most common presentation is abdominal pain, diarrhea and weight loss. It may present as subacute or even acute intestinal obstruction. Crohn’s disease is very rare in Bangladesh. Here we report a case of Crohn’s disease where the initial presentation was severe microcytic hypochromic anaemia, who received repeated blood transfusion for one year. Initially cause was not detected. Later on he presented with subacute intestinal obstruction. After all routine diagnostic work up no definitive diagnosis could be found. So laparotomy was done in Bangabandhu Sheikh Mujib Medical University (BSMMU). Histopathology report was suggestive of Crohn’s disease and he was on mesalazine with significant clinical improvement. JCMCTA 2012; 23(1): 49-50